Risk Factors for Facial Appearance Dissatisfaction Among Orthognathic Patients: Comparing Patients to a Non-Surgical Sample - Shi, Pan; Huang, Yufei; Kou, Hui; Wang, Tao; Chen, Hong (Frontiers in Psychology, 2019)
This study conducted a cross-sectional investigation of facial appearance dissatisfaction between patients before undergoing orthognathic surgery and a non-surgical sample to evaluate the potential influencing factors of facial appearance dissatisfaction. A sample of 354 participants completed a set of questionnaires concerning facial appearance dissatisfaction, interpersonal pressure, media pressure, and fear of negative appearance evaluation (112 patients, 242 controls). The patients reported higher facial appearance dissatisfaction, more media pressure, more interpersonal pressure, and a greater fear of negative appearance evaluation among others than the control group. Moreover, regression analyses identified interpersonal pressure and fear of negative appearance evaluation as the main influencing factors on facial appearance dissatisfaction whether in the orthognathic patients or in the control groups. The associations between the perceptions of interpersonal pressure, fear of negative appearance evaluation, and facial appearance dissatisfaction support the possible utility of strengthening social experiences and psychological intervention in preventing and treating these appearance-concerns, especially for the orthognathic patients.